Improved Performance Memory Module Using Verilog HDL - Dr. Khaja Mujeebuddin Quadry, D Chandrasekhar Nayak, Munyanaik Kethavath, Lavudi Srilatha (International Journal of Advanced Science and Technology, 2020)
Days and technology are growing as fast as human population. Every time technology is taking the lead over present technology. Computer systems play a key role in the present world. We are having various generations of computers like first, second, third, fourth and ultra generations. For each generation we are have improvement in the technology. From third generation onwards there is lot improvement in growth of technology. Thousand to billions of transistors are added to form very large scale integration IC chips. We are that generation where we can have end user designs based on his requirements. According to the requirements we can have on-chip setup. For every system memory is the main device, which should be handle carefully and efficient. We have synthesis memory which is not up to mark. This is build up of flip-flops. Execution process may carry with the delay Under verilog using memory module we can have 2-dimensional array registers location for more number of variables and where we can increase the speed of the programs when they are converted to active jobs. Memory is taken in form of two dimensional arrays for efficient use.